AB1133 The quality of life of children with juvenile idiopathic arthritis treated with etanercept in combination with methotrexate. (23rd January 2014) - Alexeeva, E.; Valiyeva, S.; Bzarova, T.; Isayeva, K.; Denisova, R.; Sleptsova, T.; Mitenko, E.; Fetisova, A.; Tsurikova, N.; Chomakhidze, A.
Abstract : Background: Juvenile idiopathic arthritis (JIA) - a severe, chronic, steadily progressive disease leading to early disability of patients and decreasing the QOL. The use of biologic agents for treatment of JIA, can achieve a prolonged remission of the disease and improves a prognosis. The QOL is one of the most important performance criteria of the therapy. Objectives: To assess the QOL of children with JIA treated with etanercept. Methods: 25 patients with JIA aged 8 (6, 11) years were enrolled into the study: 8 boys and 17 girls, 17of them with polyarthritis, 8 with oligoarthritis. Etanercept was administered subcutaneously twice per week at a dose of 0.4 mg/kg (maximum 25 mg), all patients received methotrexate at a dose of 15 mg/m 2 /week. The assessment of the QOL was carried out by child and parent versions of the general questionnaire PedsQL Generic Core Scale and the Childhood Health Assessment Questionnaire (CHAQ). Results: Following the patients and children assessment of QOL before the administration of etanercept the QOL in patients with JIA was significantly lower than in healthy children. Statistically significant increase in the QOL has been achieved within 4 weeks of etanercept therapy, 92% of patients improved overall score of the QOL by PedsQL questionnaire (self report from 53 to 59, according to proxy report from 49 to 60, p<0.001). Index of Functional Disability decreased in 2 times - from 2.0 to 1.0 according to CHAQ in 3 months after treatment, and was equal to 0 by 48 weeks of observation. By self-report the QOL improved physical functioning on a scale from 40 to 88 (p<0.001), on emotional functioning scale - from 60 to 89 (p<0.001), on a scale of social functioning - from 82 to 100 (p<0.001). After 12 months from the start of etanercept administration the level of the QOL for 68% of patients with JIA have been consistent with the same level of healthy children. Conclusions: Etanercept treatment significantly improves the QOL of children with JIA, reduces the negative impact of illness on the lives of children, improving physical activity and emotional state of patients, allows sick children to communicate more with other children of the same age. Disclosure of Interest: None Declared